Komparatystyczna analiza utworu Reigen Arthura Schnitzlera oraz jego tłumaczenia pt. Taniec miłości autorstwa Mariana Zbaraskiego - Janowska, Aleksandra (Migracja w języku, literaturze i kulturze, 2020)
The novel Reigen (La Ronde) written by Arthur Schnitzler – an Austrian author of Jewish origin, is an extremely crucial publication. It was written in the era of so-called Viennese modernism. The reason for its popularity is, among others, the presence of a new perception of human sexuality and numerous references to the Sigmund Freud’s theory of psychoanalysis; which, at that time, was widespread and had not only its supporters, but also a large group of opponents.In 1921, one of the first Polish translations of the novel appeared. Its author – Marian Zbarski, translated the title into Taniec Miłości (The Dance of Love.) Arguably, the work makes for an interesting literary position, due to the solutions used for text translation and the translator’s interpretation which, often enough, deviates from the original text.The purpose of this essay is to bring the reader closer to the differences between the original and the translated texts. Those dissimilarities occur mostly because of the modifications used for the translation. When conducting a comparative analysis of both texts, it is necessary to ask a question of whether and to what extent the translation by Marian Zbaraski reflects the quintessence of the original work. One may ask if the translated text is worth reading, in case it differs significantly from the original version.The answers to these questions are particularly important, because they make impartial assessment of the quality of the translation assessable. It helps the reader decide whether the translated novel is worth reading, especially if one wants to get acquainted with the work, that was not originally written in Polish.